Evaluasi Program Kelas Unggulan di MIN 1 Medan - Ahmad Mukhlasin; Abdullah Fikri Sholehuddin SN; Carles Harahap; Rizza Fikri Al-Faris (Jurnal Dirosah Islamiyah, 2024)
This research aims to explore: First, evaluate the Superior Class Program Policy at MIN 1 Medan. Second, knowing the strategies that can be implemented to optimize the Superior Class Program at MIN 1 Medan. Third, find out the obstacles faced in the MIN 1 Medan Superior Class Program Policy. This research method is a qualitative type with a descriptive approach. The instruments used in this research were observation, interviews and documentation studies. This research evaluation model uses the CIPP evaluation model, namely context, input, process and product evaluation. The location of this research is MIN 1 Medan, North Sumatra. This research data analysis uses three steps, data reduction, data presentation and conclusion drawing. The research results show that: First, the implementation of the superior class program at MIN 1 Medan includes implementing different learning from regular ones, has more complete facilities than regular ones, and learning takes longer than regular ones. Second, the planning strategy for the superior class program, namely interactive digital learning media at MIN 1 Medan, is to be more practical and carried out as early as possible so that students can easily adapt in the future. The use of digital media also helps students develop technological skills which are very important in the modern era. And facilities such as TVs are available in superior classes so that they don't use projectors which take a long time to start learning. Third, the obstacle faced in the superior class program is Training Limitations: Even though intensive training has been carried out, there are still challenges in getting an adequate amount of training for all teachers in the superior class program. Insufficient Content: At times, the availability of appropriate, quality content to support learning in top class programs can be a challenge. Time Limitations: Implementing interactive digital learning media requires additional time for preparation and development of learning content in superior class programs. Student Engagement: Although digital learning media can increase student engagement, there are also challenges in ensuring that all students can access and use the technology effectively in accordance with excellent classroom programs.